The Correlation Between Antiretroviral (ARV) Adherence and Coping Strategies on the Immune Status of People Living with HIV (PLHIV) - Fajar Ibnu Abdulrohman; Ahmad Ikhlasul Amal; Dwi Retno Sulistyaningsih (International Journal Of Health Science, 2026)
Acquired Immune Deficiency Syndrome (AIDS), caused by the Human Immunodeficiency Virus (HIV), remains a significant global health issue, with an estimated 39.9 million people living with HIV (PLHIV) worldwide. HIV damages the immune system, particularly CD4 T cells, making patients susceptible to opportunistic infections. Given this major impact, immune status is a primary focus for PLHIV, where two key factors adherence to Antiretroviral (ARV) therapy and coping strategies play a vital role. ARV adherence is proven to suppress viral replication and restore CD4 cell count, while adaptive coping strategies assist in managing stress that can weaken the immune response. To determine the correlation between ARV adherence and coping strategies on the immune status of people living with HIV (PLHIV). This study used a quantitative research type with a cross-sectional design. The sample consisted of 64 respondents. Sampling was determined using the Slovin formula technique. The data obtained were analyzed using the Spearman's Rho correlation test. The results of the Spearman's Rho correlation test indicated a correlation between antiretroviral (ARV) adherence and coping strategies on the immune status of people living with HIV (PLHIV). There is a correlation between antiretroviral (ARV) adherence and coping strategies on the immune status of people living with HIV (PLHIV).